Sex-related gut microbiota in three geographically separated Norway lobster (Nephrops norvegicus) populations - Polina Rusanova; Eleni Nikouli; Michele Casini; Gioacchino Bono; Elena Mente; Alexandra Meziti; Konstantinos Kormas (The Microbe)
Despite the ecological and economic value of the Norway lobster (Nephrops norvegicus), its gut microbiota remains largely understudied. The aim of the present study was to investigate the gut bacterial microbiota in three geographically separated N. norvegicus populations from the Mediterranean and the North Seas and detect any potential sex-related microbiota differences, by high-throughput sequencing of the V3-V4 16S rRNA gene diversity of the gut tissue. Egg-bearing females from the Greek population, were also included in this analysis. A total of 2385 operational taxonomic units (OTUs) were identified and between 417 and 1290 OTUs were present in each population/sex group. The dominant OTUs belonged to the Fusobacteriia and Bacteroidia (Sweden), Bacilli and Gammaproteobacteria (Italy) and Spirochaetia and Bacilli (Greece) bacterial classes. In the eggs, the Actinobacteria, Alphaproteobacteria and Gammproteobacteria prevailed. Four OTUs related to the Oceanispirochaeta, Kordiimonas, Desulfovibrio, Carboxylicivirga genera and one unafilliated OTU were positively correlated (p values between 0.001 and 0.04) with body size, indicating their potential role in the nutrition and growth of N. norvegicus. No statistically significant differences were found between males and females in any of the three populations. However, statistically significant differences between populations for each sex, were found for all females (p values between 0.008 and 0.032) and for the males between the most distant populations, i.e. Italy-Sweden (p = 0.021) and Greece-Sweden (p = 0.015). The egg microbiota was statistically significant different from both the adult female (p = 0.027) and male (p = 0.046) gut microbiota. Overall, this study revealed that the N. norvegicus gut microbiota is differentiated between geographically distant populations and that sex-related differences are not significant.